UJI KETAHANAN HIDUP IKAN KERAPU MACAN (Epinephelus fuscoguttatus) DENGAN TEKNIK IMOTILISASI SUHU RENDAH DALAM TRANSPORTASI SISTEM KERING - Eny Heriyati; Kasman Kasman (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2017)
Research aimed to determine survival of tiger grouper (Epinephelus fuscoguttatus) in dry transportation system. The research was conducted at Beach Fish Center of Tanjung Laut Indah bontang southern districts - East Kalimantan. Testing animals is a tiger grouper (Epinephelus fuscoguttatus) amounted 12 fishes an average weight ranging 350 - 400 grams, which is the test animals are included in consumption level and ready to be marketed. The research method uses descriptive data analysis, with 3 treatments i.e. each treatment consisting 4 groupers fish and each one transported 6, 10, and 14 hours. Each treatment is packaged in same Styrofoam with sawdust and ice cube material content that has been wrapped in newspaper and plastic. Before packing the fish beforehand was adapted for ± 24 hours and immotilitation the fish that have been ready directly using temperature 15°C for 15 minutes and fish ready to be packed in styrofoam with temperature 15°C. Obtained result from all treatments for 6 hours transportation produce survival rate (SR) level 75%, 10 hours 50%, and 14 hours 25%.